SP4.2.1 Emergency management of lower GI bleeds: a full-cycle audit of practice at a district general hospital. (9th August 2022) - Khanderia, Esha; Patel, Riana; Chandegra, Rohit; Gass, Harriet; Doshi, Akshay; Morsy, Hesham; Cheetham, Drostan
Abstract: Introduction: Lower GI bleeds (LGIB) are a common cause of emergency surgical admission. National Guidelines on the management of LGIB were published by the British Society of Gastroenterologists (BSG) in 2019. The aim of our audit was to determine whether local practice of managing LGIB adhered to these guidelines. Method: Our initial audit cycle retrospectively reviewed 47 patients with LGIB who had presented to our Hospital. Subsequently, a departmental teaching session was conducted and posters outlining BSG guidelines were placed on surgical wards and the surgical assessment unit. A re-audit of local practice was prospectively undertaken with 30 patients. Results: In the initial audit cycle 37/47 (78.7%) patients had a major LGIB (Oakland score >8) where admission is advised. Of these, 6 (16%) were discharged on the same day. Of the 10/47 (21.3%) patients who had a minor LGIB, 6 (60%) were discharged on the same day. In the re-audit cycle, 29/30 (96.7%) patients had a major LGIB and 1/30 had a minor LGIB, none of these patients were discharged on the same day. The re-audit population had a higher rate of inpatient endoscopy, 66.7% vs 14.9%. 50% of unstable patients had a CT angiogram on admission in the re-audit vs 0% patients in the first cycle. Discussion: Following education, compliance to BSG guidelines improved. Discharges in patients with major LGIB reduced to zero following this audit and more patients received appropriate inpatient investigations. Further work is required to see if change in local practice has an impact on clinical outcomes.